Spatially-resolved photocapacitance measurements to study defects in a-Si:H based p-i-n particle detectors - Casteleiro, C. (2014)
Thick large-area particle or X-ray detectors suffer degradation during operation due to creation of defects that act as deep traps. Measuring the photocurrent under homogeneously absorbed weak light can monitor variation in detector performance. We describe how photocapacitance can be used as an alternative method to measure the creation of defects and their energy level after intense irradiation with protons or He ions at 1.5 MeV and after exposure to intense laser pulses. The possibility to detect small areas of high defect density in a large-area detector structure is discussed.